Reconciling reintegration: the complexity of economic and social reintegration of ex‐combatants in Burundi. Issue 2 (28th November 2014) - Willems, Rens; van Leeuwen, Mathijs
<x xml:space="preserve">Abstract</x> The extent to which disarmament, demobilisation and reintegration (DDR) programmes initiated by state or multilateral agencies can realise the reintegration of ex‐combatants remains debated. While some consider that DDR should have the ambition to result in long‐term reintegration, others argue that DDR should focus on short‐term goals. This paper explores experiences with the reintegration of ex‐combatants in Burundi. It shows the interconnectedness of economic and social reintegration processes, and demonstrates that the reintegration of ex‐combatants cannot be seen in isolation from the wider recovery and development context in which DDR is taking place. Moreover, the case demonstrates that reconciliation and social reintegration are deeply interconnected, to the extent that social reintegration may fail if reconciliation is not taken into account. Rather than a debate between long‐ and short‐term goals, the focus should therefore be on increasing the understanding of reintegration processes and finding ways in which programmes can contribute to those.